Sustainability of E-Commerce - RuhaisalIfna, S.Sos.,MM; Sukaini, SE., MM (Cita konsultindo, 2023)
Globally, the business transition process is developing globally from conventional to digital processes so that companies need to run strategically, one way is by utilising marketing technology that leads to digital technology by utilising e-commerce. The method is done by collecting data and information related to market potential, the development of e-commerce in Indonesia and how to utilise e-commerce technology as an alternative solution in innovating marketing strategies with the aim of capturing greater market potential.